Factors Influencing the Job Satisfaction of Primary School Teachers in Rural and Urban Areas in Roorkee Taluk, Uttarakhand State - Pooja; Yenagi, Ganga V. (International Journal of Bio-resource and Stress Management, 2020)
Teachers are considered as a strongest pillar of our society. They play an important role in the growth and development of a nation by imparting knowledge and skills to young minds. As teachers are very important in any educational institution, there is a need to track on their performance, attitude and feelings. It is a management’s believe that “satisfied teachers can turn their institutions towards success” so it is very important for each and every management to identify whether their employees are really satisfied or not?. Hence, in this article an attempt has been made to identify the factors that influence the job satisfaction of primary school teachers. The present study is aimed to assess the job satisfaction of primary school teachers in Roorkee taluk of Uttarakhand state on a sample of 120 teachers. The job satisfaction was assessed by the job Satisfaction Questionnaire The findings were drawn after descriptive analysis and computed Mean, Standard Deviation and Pearson correlation. Results revealed that majority of the teachers exhibited high level of job satisfaction. The correlation analysis revealed that work experience and monthly salary had positive and significant relationship with job satisfaction of teachers in rural and urban areas while age and educational qualification of the teachers had non-significant relationship with their job satisfaction. It also revealed that teachers from government school and with higher monthly salary exhibited higher job satisfaction as compared to their counterpart. There was no gender difference found in job satisfaction of primary school teachers in both rural and urban areas.